Impaired thrombolytic status predicts adverse cardiac events in patients undergoing primary percutaneous coronary intervention - Christopoulos, Christos; Farag, Mohamed; Sullivan, Keith; Wellsted, David; Gorog, Diana A. (Thrombosis and Haemostasis, 2017)
Antithrombotic medications reduce thrombosis but increase bleeding. Identification of ST-elevation myocardial infarction (STEMI) patients at risk of recurrent thrombosis could allow targeted treatment with potent antithrombotic medications, with less potent agents in others, to reduce bleeding. Conventional platelet function tests assess platelet reactivity only, yet there is increasing evidence that endogenous thrombolytic potential determines outcome following thrombus initiation. We investigated whether assessing both platelet reactivity and endogenous thrombolysis, could identify STEMI patients at high-risk of recurrent thrombotic events. Thrombotic status was assessed in STEMI patients, before and after primary percutaneous coronary intervention (PPCI), at discharge and at 30 days; with 12 months’ followup. The time to form an occlusive thrombus under high shear (occlusion time, OT), and time to restore flow by endogenous thrombolysis (lysis time, LT) was measured using the point-of-care Global Thrombosis Test (GTT) in the cardiac catheterisation laboratory. Impaired endogenous thrombolysis (prolonged LT ≥ 3000 s), seen in 13 % patients pre-PPCI, was related to major adverse cardiac events, MACE (HR: 3.31, 95 %CI: 1.02–10.78, p = 0.045), driven by cardiovascular death (HR: 4.17, 95 %CI: 0.99–17.51, p = 0.05). Enhanced (rapid) endogenous thrombolysis (LT < 1000 s) was associated with spontaneous reperfusion, ST-segment resolution and Thrombolysis In Myocardial Infarction 3 flow pre-PPCI. Baseline OT was shorter in those with MACE (especially recurrent myocardial infarction and stroke) than those without (253 ± 150 s vs 354 ± 134 s, p=0.017). Endogenous thrombolysis, when impaired, is associated with increased cardiovascular risk, and when enhanced, with spontaneous reperfusion. Endogenous thrombolysis may be a novel target for pharmacological intervention, and allow targeting of potent antithrombotic medications to high-risk patients.
Keywords: Percutaneous coronary intervention; thrombosis; endogenous thrombolysis; myocardial infarction; coronary reperfusion